2017
DOI: 10.1007/s11356-017-8987-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar on alleviation of cadmium toxicity in wheat (Triticum aestivum L.) grown on Cd-contaminated saline soil

Abstract: Soil degradation by salinity and accumulation of trace elements such as cadmium (Cd) in the soils are expected to become one of the most critical issues hindering sustainable production and feeding the increasing population. Biochar (BC) has been known to protect the plants against soil salinity and heavy metal stress. A soil culture study was performed to evaluate the effect of BC on wheat (Triticum aestivum L.) growth, biomass, and reducing Cd and sodium (Na) uptake grown in Cd-contaminated saline soil under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(102 citation statements)
references
References 49 publications
4
98
0
Order By: Relevance
“…As discussed previously, the decrease in aluminum and cadmium toxicity by different mechanisms owing to the addition of biochar explains the higher yields of dry matter by sorghum seedlings in the BS and BB treatments. Other authors working with wheat (Abbas et al, 2017), rice (Rizwan et al, 2016), and sorghum (Soudek et al, 2016) found higher dry matter yield and lower Cd concentrations in seedlings grown in treatments with biochar, consistent with the results obtained in this study. As discussed previously, the decrease in aluminum and cadmium toxicity by different mechanisms owing to the addition of biochar explains the higher yields of dry matter by sorghum seedlings in the BS and BB treatments.…”
Section: A B Csupporting
confidence: 92%
“…As discussed previously, the decrease in aluminum and cadmium toxicity by different mechanisms owing to the addition of biochar explains the higher yields of dry matter by sorghum seedlings in the BS and BB treatments. Other authors working with wheat (Abbas et al, 2017), rice (Rizwan et al, 2016), and sorghum (Soudek et al, 2016) found higher dry matter yield and lower Cd concentrations in seedlings grown in treatments with biochar, consistent with the results obtained in this study. As discussed previously, the decrease in aluminum and cadmium toxicity by different mechanisms owing to the addition of biochar explains the higher yields of dry matter by sorghum seedlings in the BS and BB treatments.…”
Section: A B Csupporting
confidence: 92%
“…Novak et al [79] and Lehmann et al [80] also observed a significant improvement in water holding capacity of soil where BC was applied. The greater surface area and pore spaces of BC facilitate the retention of water when used in soil [33,[79][80][81]. According to Singh et al [76], the organic carbon in BC significantly facilitates PGPR for improvement in their growth.…”
Section: Discussionmentioning
confidence: 99%
“…It involved the formation of solids with PO 4 3− , CO 3 2− , Cl − or SO 4 2− either on the surface or in the solution during the adsorption process. Zhou et al [45] reported the surface precipitations for divalent metals on biochar obtained at 400 • C. Between the surfaces of the biochar and cations (Cu, Zn, Pb and Ag), there was an electrostatic attraction during the heavy metal adsorption process [46]. The variable surface charge (Q) measured for the used solids came mainly from negative surface groups.…”
Section: Cu Freundlich Isotherm Langmuir Isothermmentioning
confidence: 99%